2020
DOI: 10.1101/2020.03.23.20040501
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Containment measures limit environmental effects on COVID-19 early outbreak dynamics

Abstract: Environmental factors, including seasonal climatic variability, can strongly impact on spatio-temporal patterns of infectious disease outbreaks. We assessed the effects of temperature and humidity on the global patterns of Covid-19 early outbreak dynamics during January-March 2020. Climatic variables were the best drivers of global variation of confirmed Covid-19 cases growth rates. Growth rates peaked in temperate regions of the Northern Hemisphere with mean 5 temperature of ~5°C and humidity of ~0.6-1.0 kPa … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
112
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(130 citation statements)
references
References 85 publications
(211 reference statements)
14
112
1
3
Order By: Relevance
“…Our findings thus indicate that globalized countries could have experienced multiple and recurrent introductions of the virus via imported goods, tourists, or international exchanges of students or academics (Anzai et al, 2020;Chinazzi et al, 2020). Importantly, local climate (represented by mean temperature, precipitation and vapor pressure) was not found associated with infection rates, supporting a recent study (Luo et al, 2020) and contradicting an evaluation from 31 provincial-level regions in mainland China (Shi et al, 2020) and a global analysis (Ficetola & Rubolini, 2020). The discrepancy between our results and those from Ficetola and Rubolini (2020) may be due to the fact that they calculated exponential growth rates over a period of five days, and assessed a more limited number of predictor variables.…”
Section: Discussioncontrasting
confidence: 67%
“…Our findings thus indicate that globalized countries could have experienced multiple and recurrent introductions of the virus via imported goods, tourists, or international exchanges of students or academics (Anzai et al, 2020;Chinazzi et al, 2020). Importantly, local climate (represented by mean temperature, precipitation and vapor pressure) was not found associated with infection rates, supporting a recent study (Luo et al, 2020) and contradicting an evaluation from 31 provincial-level regions in mainland China (Shi et al, 2020) and a global analysis (Ficetola & Rubolini, 2020). The discrepancy between our results and those from Ficetola and Rubolini (2020) may be due to the fact that they calculated exponential growth rates over a period of five days, and assessed a more limited number of predictor variables.…”
Section: Discussioncontrasting
confidence: 67%
“…As the virus spreads and additional climate regions witness outbreaks of COVID-19, it is possible that the climate signal might be weakened or even lost. This could happen as consequence of varying approaches to the management of the with geographical and climate factors (39,40). We expect that the SARS-CoV-2…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, high levels of relative humidity may play a key role in viral spread, resulting in an increased virulence. In this regard, Ficetola et al (2020) recently showed that the spread of SARS-COV-2 peaked in temperate regions of the Northern Hemisphere with a mean temperature of 5 • C and a mean humidity of 0.6-1.0 kPa, while it decreased in warmer and colder regions [19]. Other studies addressed the issue of viral diffusion paying more attention to the long-range transport of pathogens associated with air masses displacement.…”
Section: Covid-19: What Evidence Is There About a Possible Airborne Rmentioning
confidence: 99%